The Impact of the Training Programme using Water environment Exercises with Laser in Partial Rupture of the Connective Muscles and the Kinetic Performance of the Football Players - Ahmed Redah Mohamed (Journal of Global Pharma Technology, 2016)
The introduction to the research has shown that the incidence of sporting activities is a phenomenon that does not correspond to the health goals of the athlete, and the injuries are not limited to higher levels but are at all levels. football is one of the most aesthetic and vulnerable games and its various forms, both for the competitor and for the player itself, the limited use of modern methods and techniques used in rehabilitation that do not result from the use of any negative side effects and can be used for all ages, different stages and all parts of the body in order to increase the impact on the maximum level of rehabilitation of the injured and return to the practice Sports activities. Hence the importance of research in the establishment of exercises within and outside the aquatic environment and through the laser in rehabilitating those with connective muscle rupture and solving the problem as soon as possible, and the problem of research is that there is a lack of rehabilitative curricula that take practice within and outside the aquatic environment for the rehabilitation of infected players and that most Rehabilitation programmes related to the treatment of the connective muscles lack the use and disregard of modern methods and techniques during the rehabilitation of the injured in such type of infection (the rupture of the connective muscles) and the return of the athlete to the exercise of athletic activity before reaching full recovery.The Research objectives to:Preparation of rehabilitation exercises within the water environment in order to rehabilitate and improve the partial rupture of the connective muscles and the kinetic performance of football players who represent the clubs of the governorate of Baghdad.Identification of the effect of the rehabilitation programme using in-house exercises with the laser in the partial rupture of the connective muscles and the kinetic performance of the football players.Recognition of the preference for the impact of tests (Pretests and posttests) on the members of the experimental search sample.The research hypotheses are as follows:Exercises prepared within the water environment have a positive effect in the rehabilitation and improvement of the partial rupture of the muscles of the plug and the performance of motor for football players. There is a positive effect in the members of the group that used exercises within the water environment accompanied by the laser in the rehabilitation and improves the partial rupture of the muscles of the plug and the performance of motor for football players.There is a preference for the effect between tests (Pretests and posttests) and in to post-test.The search sample (10) included players with partial rupture of the connective muscles, and the researcher used the experimental method to fit the nature of the research as the researcher carried out the pretests tests, after which the qualifying program was applied for 8 weeks, in the case of (3) weekly units, and after the completion of the application Qualifying program the researcher performed the following tests to extract the results after presenting, analyzing and discussing them and to see the significance of the differences between the tests and the extent to which the program contributed to the development of the variables.A number of conclusions were reached:Exercise within the water environment and the laser device helped to improve the motor performance and strength of the macrophages of the injured players.Was the best development for the tests of fitness and strength of the connective muscle and the degree of pain in favor of the post-test?Keywords: Training programme, Water environment, Partial rupture and connective muscles.